Reproductive biology of the smooth butterfly ray Gymnura micrura - Yokota, L. [UNESP]; Goitein, R. [UNESP]; Gianeti, M. D.; Lessa, R. T. P. (Wiley-Blackwell, 2012)
This study provides the first detailed information on the reproductive biology of the smooth butterfly ray Gymnura micrura. A total of 905 individuals were sampled, 377 of which were used for the reproductive study. Juveniles accounted for 75% of the sample, but all life cycle stages were present in the study area. The disc width at which 50% were mature (WD50)was estimated at 269 and 405 mm for males and females, respectively. The WD50V(based on the onset of vitellogenesis) was estimated at 359 mm. Uterine fecundity (mean +/- s.d. = 3.8 +/- 1.3; range: 16) was positively correlated with female size. A 3564% gain in mean wet mass was observed from egg to full-term embryo in utero. Size at birth ranged from 135 to 175 mm WD (19.5 to 55.0 g), with a mean of 165.1 mm WD (43.3 g). The embryo sex ratio was not significantly different from 1:1. The ovaries of pregnant females were undergoing vitellogenesis during gestation, with females ready to ovulate soon after parturition. Gymnura micrura may have an asynchronous reproductive cycle, with females reproducing continuously throughout the year.
Keywords: elasmobranch; Myliobatiformes; north-eastern Brazil; reproduction; tropical region